(untitled) (American Journal of Islam and Society, 2005)
Jeffrey Lang is a well-known Muslim convert and professor of mathematics at the University of Kansas. Losing My Religion is his third book. In many ways, it surpasses the first two in the relevance and urgency of its subject matter. While the book shares its title with a 1991 song by the popular rock band REM, its central theme is almost as old as religion itself: bridging the chasm that seems to separate religious beliefs and practices on the one hand, and contemporary rationality and secular culture on the other. Perhaps because of his background in mathematics, Lang is confident that human reason, if properly used, can and will affirm the truths of divine revelation. The idea is by no means new, though its application has always called for the most rigorous efforts by the most sophisticated human intellects. Writing as a lay theologian, Lang makes some interesting points in Losing My Religion, which is primarily aimed at the general North American Muslim community. The main impetus behind this book is the alienation experienced by young Muslims and converts who are confronted with the traditional and conservative forms of Islam presented (and vigorously defended) by the immigrant-dominated mosque culture. This alienation accounts for the facts that the majority of second- and third-generation Muslims tend to stay away from mosques and that it is generally the older immigrants or very recent arrivals who seem to be active in these institutions. Lang rightly argues that the young people’s absence from the mainstream of the Muslim community’s religious and social life represents a serious threat to Islam’s survival and growth in North America ...